2005
DOI: 10.1007/s00425-005-1492-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ploidy stability of the somatic embryogenesis process in Quercus suber L. using flow cytometry

Abstract: Flow cytometry analyses were used to verify the ploidy stability of Quercus suber L. somatic embryogenesis process. Leaf explants of two adult cork oak trees (QsG0 and QsG5) of the North of Portugal were inoculated on MS medium with 2,4-D and zeatin. After 3 months, calluses with embryogenic structures were isolated and transferred to fresh MS medium without growth regulators and somatic embryo evolution was followed. Morphologically normal somatic embryos (with two cotyledons) and abnormal somatic embryos (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 38 publications
4
52
0
Order By: Relevance
“…By this approach, the cumbersome method of repeated backcrossings is achieved in one step. Problems of identification of the cellular origin and genotypic composition of anther-derived embryos were overcome through the use of molecular markers, i.e., enzymes and random amplified polymorphic DNA (RAPD; Bueno et al, 2000) and simple sequence repeats (SSR;Gomez et al, 2001), by ploidy level studies through flow cytometry (Bueno et al, 2003;Loureiro et al, 2005), and by cytological analysis of early microspore divisions (Pintos et al, 2005). All these methods corroborated the gametic origin and the genetic variability of the anther embryos from different haploid cells (microspores).…”
Section: Introductionmentioning
confidence: 99%
“…By this approach, the cumbersome method of repeated backcrossings is achieved in one step. Problems of identification of the cellular origin and genotypic composition of anther-derived embryos were overcome through the use of molecular markers, i.e., enzymes and random amplified polymorphic DNA (RAPD; Bueno et al, 2000) and simple sequence repeats (SSR;Gomez et al, 2001), by ploidy level studies through flow cytometry (Bueno et al, 2003;Loureiro et al, 2005), and by cytological analysis of early microspore divisions (Pintos et al, 2005). All these methods corroborated the gametic origin and the genetic variability of the anther embryos from different haploid cells (microspores).…”
Section: Introductionmentioning
confidence: 99%
“…Loureiro et al (2005), using flow cytometry, found no ploidy or DNA content variations in cork oak embryogenic tissues or among somatic embryos ( Figure 5). …”
Section: Screening Of Genetic Variation In Cloned and Cryopreserved Mmentioning
confidence: 94%
“…In particular, the currently available rates of success in cork oak plant regeneration by somatic embryogenesis Lopes et al, 2006;Loureiro et al, 2005;Pinto et al, 2001;2002) and in cork oak material cryopreservation (Fernandes et al, 2008;Fernandes, 2011) are highly encouraging for researchers and breeders to consider the integration of these strategies in breeding and conservation programs of this species (Figure 1). …”
Section: Quercus Suber In Vitro Cloning: a Reliable Protocol?mentioning
confidence: 99%
See 2 more Smart Citations